The Effect Of The Discovery Learning Learning Model on Mathematical Critical Thinking Abilities Students In Class X - Nova Febriana Simbolon; Rianita Simamora; Rick Hunter Simanungkalit (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the effect of the Discovery Learning learning model on the mathematical critical thinking skills of students in grade X of Sma Negeri 5 Pematangsiantar in the academic year 2025/2026. This type of research is quantitative research. The method used by the researcher is the experimental method. This research method was chosen to see how much influence the Discovery Learning learning model has on students' mathematical critical thinking skills on the material of Arithmetic Sequences and Series at Sma Negeri 5 Pematangsiantar. According to (Sugiyono, 2021) there are several forms of experimental design, namely: 1) Pre-experimental (nondesign); 2) True-experimental and; 3) Quasi-experimental. The research design used in this study is Pre-experimental (nondesign). This research was only conducted using an experimental class without a control class. Based on the results of data analysis and discussion, it can be concluded that there is a significant influence of the Discovery Learning Model on Students' Mathematical Critical Thinking Skills on Arithmetic Sequences and Series Materials at SMA Negeri 5 Pematangsiantar. This influence can be seen from the regression equation Y^^=-6.179+0.606X with a regression coefficient of 0.606 and a large determination coefficient of 71% which indicates that there is a very strong relationship between the Discovery Learning Model and Students' Mathematical Critical Thinking Skills.